Analisis Penyebab Penyalahgunaan Tramadol oleh Remaja di Johar Baru Jakarta Pusat Berdasarkan Differential Association Theory - Riska Syaira Kinsi; Nadia Utami Larasati (Anomie, 2019)
This thesis discusses teenagers who abused tramadol. Where in doing the abuse of tramadol drugs, teenagers do voluntarily. Tramadol is one of narcotic analgesic drugs. The theory that is used by researchers to conduct analysis is Differential Association Theory. The theory states that the abuse of tramadol is learned. This research use qualitative method because researchers want to understand the phenomena that occured holistically and by describing events in the form of words and languages. The result of the data obtained by the researchers showed that the abuse of tramadol by adolescents is learned through personal communication and general learning techniques.